Influence of microgap location and configuration on the periimplant bone morphology in submerged implants. An experimental study in dogs - Weng, Dietmar; Nagata, Maria José Hitomi [UNESP]; Bell, Matthias; Bosco, Álvaro Francisco [UNESP]; Nascimento de Melo, Luiz Gustavo [UNESP]; Richter, Ernst-Juergen (Wiley-Blackwell, 2008)
Objectives: The vertical location of the implant-abutment connection influences the periimplant bone morphology. It is unknown, however, whether different microgap configurations cause different bone reactions. Therefore, in this study the bone morphologies of two different implant systems were compared.Material and methods: Three months after tooth extraction in eight mongrel dogs, two grit-blasted screw implants with internal Morse taper connection (ANK group) were placed on one side whereas the contralateral side received two oxidized screw implants with external hex (TIU group). One implant on each side was placed level with the bone (equicrestal), the second implant was inserted 1.5mm below bone level (subcrestal). After 3 months the implants were uncovered. Three months after stage two surgery, histometrical evaluations were performed in order to assess the periimplant bone levels (PBL), the first bone-to-implant contact points (BICP), the width (HBD) and the steepness (SLO) of the bone defect.Results: All implants osseointegrated clinically and histologically. Bone overgrowth of the microgap was seen in ANK implants only. No significant differences between ANK and TIU could be detected in neither vertical position for PBL and BICP. However, a tendency in favor of ANK was visible when the implants were placed subcrestally. In the parameters HBD (ANK equicrestal -0.23mm; TIU equicrestal -0.51mm; ANK subcrestal +0.19mm; TIU subcrestal -0.57mm) and SLO (ANK equicrestal 35.36 degrees; TIU equicrestal 63.22 degrees; ANK subcrestal 20.40 degrees; TIU subcrestal 44.43 degrees) more pronounced and significant differences were noted.Conclusions: Within the limits of this study, it is concluded that different microgap designs cause different shapes and sizes of the periimplant ('dish-shaped') bone defect in submerged implants both in equicrestal and subcrestal positions.
Keywords: bone morphology; equicrestal placement; histometric study; microgap; subcrestal placement